Understanding the track and field sprint start through a functional analysis of the external force features which contribute to higher levels of block phase performance - Bezodis, N. E.; Walton, S. P.; Nagahara, R. (Journal of Sports Sciences, 2019)
This study aimed to identify the continuous ground reaction force (GRF) features which contribute to higher levels of block phase performance. Twenty-three sprint-trained athletes completed starts from their preferred settings during which GRFs were recorded separately under each block. Continuous features of the magnitude and direction of the resultant GRF signals which explained 90% of the variation between the sprinters were identified. Each sprinter`s coefficient score for these continuous features was then input to a linear regression model to predict block phase performance (normalised external power). Four significant (p < 0.05) predictor features associated with GRF magnitude were identified; there were none associated with GRF direction. A feature associated with greater rear block GRF magnitudes from the onset of the push was the most important predictor (ß = 1.185), followed by greater front block GRF magnitudes for the final three-quarters of the push (ß = 0.791). Features which included a later rear block exit (ß = 0.254) and greater front leg GRF magnitudes during the mid-push phase (ß = 0.224) were also significant predictors. Sprint practitioners are encouraged, where possible, to consider the continuous magnitude of the GRFs produced throughout the block phase in addition to selected discrete values.